Masalah Belajar yang Dialami Oleh Peserta Didik dalam KBM Pada Kelas 5 di SD Negeri 03 Probur Utara - Gaudensius S. Yenifana; Yerimia S. Wabang; Pilmon Karmaley; Saaltiel Mohar (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2024)
Learning problems are certain conditions experienced by students and hinder the smooth process carried out by individuals to obtain a new change in behavior as a whole. Certain conditions can be related to their condition, namely in the form of weaknesses and can also be related to an environment that is not beneficial to them. These learning problems are not only experienced by students who are slow in learning, but can also befall students who have above average abilities, are smart or intelligent.